Benign Multicystic Peritoneal Mesothelioma: Two Rare Cases and Review of the Literature - Incesu, Mustafa Mehmet; Ucar, Murat; Kozan, Ramazan; Simsek, Berkay; Esendagli, Guldal (Current Medical Imaging, 2024)
BackgroundBenign multicystic peritoneal mesothelioma is a multiloculated cystic mass which originates from the peritoneum. This rare tumor is usually seen in women of childbearing age and has a high recurrence rate after surgery.Case PresentationWe present two benign multicystic peritoneal mesothelioma cases with different imaging modalities, which were also pathologically proven.ConclusionThe imaging features which may be diagnostic should be well known as there are very few reports regarding this entity.
Keywords: Multicystic mass